Peran Bimbingan dan Konseling dalam Meningkatkan Kemampuan Self- Regulation Siswa Menengah ke Atas di Sekolah X - Maghfirotunnizar, Meyla; Aliffianto, Fahira (Jurnal Konseling dan Psikologi Indonesia, 2025)
The problems currently being experienced by high school students in grade XI are the lack of time management and completing assignments on time due to the low self-regulation of students based on the results of interviews with guidance and counseling teachers. The purpose of this study was to determine the role of guidance and counseling in school X in overcoming this phenomenon. The research method used was qualitative with data collection techniques, namely interviews and literature studies as supporting methods. The main findings in this study were that guidance and counseling teachers tried to provide programs and interventions in developing time management skills. This study revealed the challenges of students having good self-regulation and the importance of schools, especially guidance and counseling teachers, in helping students face challenges in order to achieve their maximum potential at school.